1993
DOI: 10.1007/bf00189885
|View full text |Cite
|
Sign up to set email alerts
|

Head-on collision of normal shock waves with rigid porous materials

Abstract: The head-on collision of a planar shock wave with a rigid porous material has been investigated experimentally in a 75 mm x 75 mm shock tube. The experimental study indicated that unlike the reflection from a flexible porous material (e.g., polyurethane foam) where the transmitted compression waves do not converge to a sharp shock wave, in the case of a rigid porous material (e.g., alumina) the transmitted compression waves do converge to a sharp shock wave, which decays as it propagates along the porous mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 14 publications
(8 reference statements)
4
40
1
Order By: Relevance
“…Instead, a filtration process during which the pressure on the wall increases gradually takes place (Seitz & Skews 1996;Britan et al 2001Kitagawa et al 2006;Britan, Shapiro & Ben-Dor 2007). This filtration effect is well documented for rigid porous media, in which the porous skeleton remained rigid when impinged by a shock wave (Levy et al 1993;Levy, Ben-Dor & Sorek 1996a, 1998Andreopoulos, Xanthos & Subramaniam 2007;Kazemi-Kamyab, Subramaniam & Andreopoulos 2011). In their investigations rigid porous samples were placed either adjacent to the supporting wall or with a predetermined gap, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Instead, a filtration process during which the pressure on the wall increases gradually takes place (Seitz & Skews 1996;Britan et al 2001Kitagawa et al 2006;Britan, Shapiro & Ben-Dor 2007). This filtration effect is well documented for rigid porous media, in which the porous skeleton remained rigid when impinged by a shock wave (Levy et al 1993;Levy, Ben-Dor & Sorek 1996a, 1998Andreopoulos, Xanthos & Subramaniam 2007;Kazemi-Kamyab, Subramaniam & Andreopoulos 2011). In their investigations rigid porous samples were placed either adjacent to the supporting wall or with a predetermined gap, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Numerical simulations with the one-dimensional version of this model (Levy et al, 1996) proved to yield excellent agreement with experimental observations, concerning almost nondeformable porous materials. The results of the experimental study of Levy et al (1993) with 40 mm long sample made of SiC having 10 pores per inch and an incident-shock-wave Mach number of 1.378, for the pressure histories of air at various locations along the shock tube, are presented in Figure 1. In Levi-Hevroni et al (2002), following Levy et al (1995), we consider a solid matrix that is capable to undergo extremely large deformations.…”
Section: Shock Waves Through a Highly Deformable Porous Mediummentioning
confidence: 99%
“…To verify the performance of this approach, simulations were compared against the shock tube experiments of Levy et al (1993) and the onedimensional simulations (Levy et al, 1996) of a porous matrix undergoing small deformations. The gas pressure histories upstream of the porous material, on the side-wall inside the porous material and at the end-wall are shown in Figure 1(a)-(c), respectively.…”
Section: Shock Waves Through a Highly Deformable Porous Mediummentioning
confidence: 99%
“…standoff distance (SOD), between the rear face of the porous sample and the shock tube end wall. The investigations revealed that the pressure that was developed on the end wall was affected by the shock wave strength, the fluid properties, the porous sample properties and the standoff distance, which determines the volume of the abovementioned air gap (Levy et al 1993 In more recent research, Kazemi-Kamyab et al (2011) studied experimentally the stress transmitted to the end wall of a shock tube shielded by a rigid porous medium. They showed that the introduction of a fixed air gap between the porous sample and the end wall decreased the stress transmitted to the end wall.…”
mentioning
confidence: 99%
“…Shock interaction with a rigid porous medium Skews, Atkins & Seitz (1992), Levy et al (1993), Levy, Ben-Dor & Sorek (1996, 1998, Andreopoulos, Xanthos & Subramaniam (2007) and Kazemi-Kamyab et al (2011) have conducted several studies on the interaction of shock waves with rigid porous media in which the skeleton of the porous medium remained incompressible when impinged by the shock waves. In these studies, the filtration effect was well documented to be the governing mechanism affecting the shock wave passage through the porous medium and the development of the flow field inside and in the vicinity of the porous medium.…”
mentioning
confidence: 99%